If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 13 = 12 + 9x Reorder the terms: 13 + 4x = 12 + 9x Solving 13 + 4x = 12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 13 + 4x + -9x = 12 + 9x + -9x Combine like terms: 4x + -9x = -5x 13 + -5x = 12 + 9x + -9x Combine like terms: 9x + -9x = 0 13 + -5x = 12 + 0 13 + -5x = 12 Add '-13' to each side of the equation. 13 + -13 + -5x = 12 + -13 Combine like terms: 13 + -13 = 0 0 + -5x = 12 + -13 -5x = 12 + -13 Combine like terms: 12 + -13 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2
| 54+15x=72+6x | | 5x+63=12x+35 | | 10x+14=3x+42 | | 5x+90=15x+40 | | 6x+32=24+10x | | 36+14x=63+5x | | 12+10x=18+7x | | 6x+24=9x+6 | | 36+14x=72+5x | | 12+8x=4x+36 | | 8x+42=14x+36 | | 6x+28=16+10x | | 8+7x=10+5x | | 5x+42=12x+14 | | 3x+7+2(3+x)= | | 4x+10=2+6x | | 24+7x=12+10x | | 2x+30=10+7 | | 42+4x=10x+24 | | 3x+7+3(3+x)= | | 20+15x=70+5x | | 66+12x=1x+88 | | 6x+64=14x+48 | | 7x+40=10+12x | | (5/6x)-2x=(5/3)-(8/3) | | 33+14x=55+3x | | 8+3x=4+7x | | 32+13x=5x+48 | | 66+2x=13x+55 | | 18+11x=5x+30 | | 14x+24=2x+72 | | 3x+50=13x+30 |